Thor - Braun, Eric 1971- (Mankato, Minnesota : Black Rabbit Books, 2018)
"Through engaging text and dynamic infographics, describes the mythical stories of the Norse god Thor"--
An ancient story -- Norse mythology -- God of the sky and thunder -- The final battle.
Includes bibliographical references and index.
Age 9-12.
Grade 4 to 6.
Accelerated Reader
108059
Keywords: Thor -- (Norse deity) -- Juvenile literature; Thor -- (Norse deity); Mythology, Norse -- Juvenile literature; Mythology, Norse; Literature; Juvenile works